Web-Based Attendance and Leave Management System with Sequential Search Implementation at Tondano Religious Court - Rorimpandey, Gladly C.; Rombon, Natalia Arsel; Kainde, Quido C (Informatika, Universitas Jenderal Soedirman, 2026)
Based on the problems found in the leave application and attendance recording processes at the Religious Court of Tondano, this research was conducted to address these issues through the implementation of the Sequential Search Algorithm in a web-based application. This application aims to manage leave requests and employee attendance efficiently. The existing manual processes, such as paper-based attendance sheets and leave forms requiring multiple physical signatures, have proven to be inefficient, prone to manipulation, and at risk of data loss. To solve these issues, the application was developed using the Rapid Application Development (RAD) method, which enables a faster process in planning, designing, and deploying the system. The implementation of the Sequential Search Algorithm allows for efficient data retrieval, particularly in searching employee leave data without requiring data sorting, thereby simplifying the search process. In addition, the system includes a location-based attendance feature to prevent fraud, ensuring that employees are present within a defined radius before marking attendance. This online system benefits both permanent and non-permanent employees by providing a more secure, accurate, and accessible record of attendance and leave history. This research contributes to the digital transformation efforts of the Religious Court of Tondano by offering an integrated system that supports internal Administration processes and improves overall service quality through the use of information technology.